Analiza vetrnega potenciala na Primorskem z vidika možnosti za proizvodnjo električne energije - Peršolja, Karol Peter (Strojniški vestnik, 2004)
Modern society is based on the use of electrical energy. Electricity blackouts, which have occurred in some countries in recent years, have revealed how dependent society is on electrical energy. The unpredictability of oil prices and the fact that fossil fuels will be exhausted in the future, force mankind to investigate new energy sources, which must be sustainable, cheap and environmentally friendly. Wind is an example of such an apparently inexhaustible energy source. The exploitation of wind energy is technologically possible. Wind power plants are already included in the electro-energy systems of Denmark, Germany, the USA, Spain and many other countries. In Slovenia, electricity is not yet produced from wind energy. The purpose of this article is to examine whether the wind energy available in thewindiest part of Slovenia, the Coastal region, is sufficient to allow economical electricity production using wind power plants.
Keywords: elektrarne na veter; hitrost vetra; potencial vetra; porazdelitev Weibullova; energija vetra; Primorska; Slovenian Littoral; Slovenija; Slovenia